Mark - Strauss, Mark L.; Arnold, Clinton E. (Grand Rapids, Michigan : Zondervan, 2014)
Mark's fast-paced, powerful, and dramatic gospel takes the reader on a breathtaking tour through the life, death, and resurrection of Jesus the Messiah, the most important person in human history. Mark Strauss uses a narrative and theological approach to provide insight into the evangelist's storytelling craft, theological purpose, and narrative themes. The author stresses both the message of Jesus as he proclaims the kingdom of God and the mission of Jesus as he suffers and dies as a ransom for human sin. In turn, Jesus calls us to be his disciples and live in obedience to that kingdom calling in our lives. -- Book Cover.
Series introduction -- Author's preface -- Abbreviations -- Introduction to Mark -- Select bibliography -- Commentary on Mark -- The endings of Mark's Gospel -- The theology of Mark -- Scripture index -- Subject index -- Author index.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries